2016
DOI: 10.1149/2.0951606jes
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Revisiting Thin Foil Penetration Technique for Intergranular Corrosion Tests on Aluminum Alloys

Abstract: The measurement of the penetration time by detecting the resistance change in a piece of filter paper sandwiched between the back of the foil sample and a copper foil, which was conventionally applied in thin foil penetration experiments, was modified. This preliminary study aims to validate the optical detection of the leakage of the electrolyte on the opposite side of very thin foils of AA2024 (30 μm in thickness) due to the full penetration of intergranular corrosion. Evaluation of the potential of this app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The corrosion behavior of such a thin foil was studied in a previous work related to the application of the thin foil penetration technique on this kind of thin target . During immersion tests (in 0.1 M NaCl solution) under potentiostatic conditions, it was demonstrated that the alloy is sensitive to IGC.…”
Section: Methodsmentioning
confidence: 99%
“…The corrosion behavior of such a thin foil was studied in a previous work related to the application of the thin foil penetration technique on this kind of thin target . During immersion tests (in 0.1 M NaCl solution) under potentiostatic conditions, it was demonstrated that the alloy is sensitive to IGC.…”
Section: Methodsmentioning
confidence: 99%
“…13 The complementary methodology improvements, i.e. the control of the IGC initiation and the chemical analysis of the electrolyte trapped inside the grain boundary network, will be described and applied to assess quantitatively the IGC propagation on Al-Cu alloys.…”
mentioning
confidence: 99%
“…13 Compared to this preliminary work 13 carried on TL * L exposed surfaces for which penetrating IG paths presented an important tortuosity, in this work, the IGC propagation was studied in the L direction to approach the intrinsic propagation rate, as explained before. The optical detection consisted in detecting the purged electrolyte trapped in the "IG crevice" cavities emerging along full penetrating defects and forming droplets (Figure 2a).…”
mentioning
confidence: 99%
See 2 more Smart Citations